2013
DOI: 10.1371/journal.pone.0054000
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Chimeric Soluble Fas Ligand Polymer with In Vivo Anti-Tumor Activity

Abstract: Binding of ligand FasL to its receptor Fas triggers apoptosis via the caspase cascade. FasL itself is homotrimeric, and a productive apoptotic signal requires that FasL be oligomerized beyond the homotrimeric state. We generated a series of FasL chimeras by fusing FasL to domains of the Leukemia Inhibitory Factor receptor gp190 which confer homotypic oligomerization, and analyzed the capacity of these soluble chimeras to trigger cell death. We observed that the most efficient FasL chimera, called pFasL, was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Indeed, the sFasL from patients was found to be bioactive and present as high molecular weight multimers and aggregates [21]. Daburon et al [22] also reported that a chimeric sFasL in its oligomerized form is cytotoxic and displays antitumor activity. We can hypothesize that, in our case, sFasL from sera of patients with bladder carcinomas could exist in aggregated forms, explaining its cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the sFasL from patients was found to be bioactive and present as high molecular weight multimers and aggregates [21]. Daburon et al [22] also reported that a chimeric sFasL in its oligomerized form is cytotoxic and displays antitumor activity. We can hypothesize that, in our case, sFasL from sera of patients with bladder carcinomas could exist in aggregated forms, explaining its cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a polymeric dodecamer FasL chimera was described in which FasL was fused to the homotypic aggregation domain of Leukemia Inhibitory Factor receptor gp1909. This multimeric FasL chimera also proved highly active in vitro , possessed tumoricidal activity in vivo , and had no liver toxicity at tumoricidal concentrations [59]. Thus, it is possible to design sFasL variants that possess a clear therapeutic window, at least in murine model systems.…”
Section: Fas-ligand (Fasl)mentioning
confidence: 99%
“…We did not observe any effect of co-expressed sFasL on the net production of trimeric sfFasL, likely because it is already produced at saturating levels when expressed alone in the optimized experimental conditions used. For pfFasL, which is polymeric [21], the production of this chimera is enhanced by up to 10 fold in the presence of sFasL. For more complex FasL-based chimeras, such as HLA-pfFasL and TCR-pfFasL, production is also improved, but to a lower 2 to 5 fold range.…”
Section: Discussionmentioning
confidence: 99%
“…The soluble FasL (sFasL) and the soluble polymeric FasL (pFasL) constructs were previously described [21]. Regarding the TCR-pFasL, two constructs were generated by fusing the extracellular regions of the γ4 TCR chain (aa 20 to 295) or of the δ5 TCR chain (aa 27 to 272) to the pFasL coding sequence as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation